Assessment of Growth Enhancement Cayenne Pepper with Organic Inducer Biomass and Mycorrhizae - ambar susanti; Muhammad Miftachul Amri; Agus Suhadi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to determine the effect of the addition of organic inducer biomass and Arbuscular Mycorrhiza Fungi (AMF) on the vegetative growth of Cayenne pepper (Capsicum frutescens l.). The study was conducted in Cupak Village, Kudu District, Jombang Regency, April to July 2025. The research method used was a non-factorial randomized block design (RAK) with 5 treatments and 5 replications. The treatments tested consisted of negative control (k-), positive control (k+), and a combination of BIO (organic fertilizer made from bamboo leaves, goat manure, rice husks, and EM4) and AMF, namely P1 (75% bio + 25% soil + AMF), P2 (50% bio + 50% soil + AMF), and P3 (25% bio + 75% soil + AMF). The parameters observed included plant height, number of leaves, length and fresh weight of roots. Data were analyzed using ANOVA test and continued with Tukey test at 5% level for significant difference test. The results showed that the application of BIO and AMF significantly increased the height of chili pepper plants at 35 and 42 days after planting (DAP). Treatment P3 produced the best results, with plant height reaching 17.9 cm at 42 DAP, a highly significant difference compared to the other treatments. Leaf number, length, and root fresh weight showed a trend toward increasing, but statistical analysis showed no significant differences (p > 0.05). The results indicated that the combination of BIO and AVM has the potential to increase the vegetative growth of chili pepper, particularly plant height compared to the control